Comparative analysis of spatial ability in immersive and non-immersive virtual reality: the role of sense of presence, simulation sickness and cognitive load - Thorp, Sebastian Oltedal; Rimol, Lars Morten; Lervik, Simon; Evensmoen, Hallvard Røe; Grassini, Simone (Frontiers in Virtual Reality, 2024)
This study investigates the effects of immersion on spatial ability in virtual reality (VR) and the influence of sense of presence, simulation sickness, and cognitive load. Participants performed a spatial ability task using a head-mounted display in an immersive or non-immersive VR condition. Contrary to expectations, immersive VR did not enhance spatial performance compared to non-immersive VR. Interestingly, cognitive load was positively associated with spatial ability in immersive VR but negatively associated with it in non-immersive VR. A higher sense of presence was associated with increased spatial ability for both conditions. Predictably, simulation sickness negatively impacted spatial ability in the more immersive condition. Sense of presence and simulation sickness correlated in the immersive condition but not in the non-immersive condition, indicating the importance of immersion as a covariate. These findings highlight a complex interplay of factors in immersive environments, challenging existing assumptions and providing insights for designing spatial environments in immersive and non-immersive virtual environments.